Eksplorasi Media Pembelajaran Bahasa: Implikasi pada Siswa - Setyawan Pujiono; Maman Suryaman; Sulis Triyono (Badan Pengembangan dan Pembinaan Bahasa, 2023)
Learning media is one of the important factors determining the success of the language learning process. The media will facilitate the work of teachers in carrying out the transfer of knowledge to students. In this regard, this study aims to (1) describe the suitability of the use of media in planning (RPP) with the implementation of language learning in the classroom, and (2) describe students' responses to the use of language learning media. Indonesian language learning media in public junior high schools in Sleman Regency. Qualitative and quantitative descriptive is research methods. Qualitative methods are carried out through observation instruments, interviews, and document analysis. The quantitative method is carried out through a questionnaire instrument. The research population is teachers and students of public junior high schools in Sleman Regency. The sampling technique used purposive sampling with strata technique (high, medium, low). The data analysis technique was descriptive qualitative and quantitative. The results of the study show that: first, the use of instructional media in planning and implementation is not appropriate. The learning media used by the teacher during learning are visual, conventional, and audio visual media. Second, students' responses to the use of learning media are categorized as good. The use of learning multimedia by teachers serves to stimulate thoughts, feelings, attention, and motivate students to learn so that language learning becomes more meaningful. AbstrakMedia pembelajaran merupakan salah satu faktor penting penentu keberhasilan proses pembelajaran bahasa. Media akan mempermudah kerja guru dalam mentransfer ilmu pengetahuan kepada siswa. Terkait dengan hal itu, penelitian ini bertujuan (1) mendeskripsikan kesesuaian penggunaan media di perencanaan (RPP) dengan pelaksanaan pembelajaran bahasa di kelas dan (2) mendeskripsikan tanggapan siswa terhadap penggunaan media pembelajaran bahasa. Metode penelitian ini adalah deskriptif kualitatif dan kuantitatif. Metode kualitatif dilakukan melalui instrumen pengamatan, wawancara, dan analisis dokumen. Adapun metode kuantitatif dilakukan melalui instrumen angket. Populasi penelitian adalah guru dan siswa SMP Negeri di Kabupaten Sleman. Teknik pengambilan sampel menggunakan purposive sampling dengan teknik strata (tinggi, sedang, dan rendah). Teknik analisis data dengan cara deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa: pertama, penggunaan media pembelajaran pada perencanaan dan pelaksanaan tidak sesuai. Media pembelajaran yang digunakan guru saat pembelajaran adalah media visual, konvensional, dan audio visual. Kedua, tanggapan siswa terhadap penggunaan media pembelajaran berkategori baik. Penggunaan multimedia pembelajaran oleh guru berfungsi untuk merangsang pikiran, perasaan, perhatian, dan memotivasi peserta didik untuk belajar sehingga pembelajaran bahasa menjadi lebih bermakna.